PENINGKATAN HASIL BELAJAR PASSING PADA PERMAINAN SEPAK BOLA MELALUI PERMAINAN GAWANG BERALIH UNTUK PEMBELAJARAN PENJASORKES SISWA SD NEGERI CANDIREJO 01 KAB. BATANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Results of this research is a model learning in sports physical education and health learning of passing study change gate’s game . The based result of supervision soccer learning, especially of passing lesson in students class IV of SD N Candirejo 01 not yet realize by right, because opportunity of passing movement’s students is still less. The data of percentages learning result only 53% can be evidence that result is no more rests on the standards of learning results. The according of this description, researcher to seek result of passing learning through through change gate’s game to purpose application concept of passing movement on football’s games by modifications of games to increase movement student’s activities. So that, it can breaking of fear students and improvement of passing learning on football’s game. The analysis of cycle I have percentage 70%, in cycle II increase be 88% and total of completeness are 26 students. The conclusions of result is learning through a modification of change gate’s game can increase passing learning.